Location effects on forage production and quality among selected pioneer corn hybrids - Tiemann, D.G.; Bolsen, K.K.; Clark, D.H.; Kezar, W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Six Pioneer corn hybrids were grown in Kansas and four of the six hybrids within three locations in Utah. The Utah hybrids were harvested between the one-quarter and one-half milk line stages of kernel maturity, whereas the Kansas hybrids were harvested at approximately 90% of kernel maturity. Location had a significant effect on the agronomic characteristics and chemical composition of the hybrids. Whole-plant dry matter (DM) and digestible DM yield, grain yield, and percent grain were higher in the Kansas-grown corn. The greater yield and proportion of grain were results of the excellent growth conditions i n 1992 and their advanced stage of kernel maturity at harvest. Experimental hybrid X0811 yielded the highest whole-plant DM, grain, stover, and digestible DM among the Kansas corns. Hybrid X0811 also had the highest whole-plant and stover in vitro DM digestibility (IVDMD), the highest whole-plant and stover crude protein (CP), and the lowest whole-plant and stover neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents among the Kansas corns. Hybrid X0811 had the highest stover and digestible DM yields, whole-plant C P and IVDMD, and stover IVDMD and the lowest stover NDF and ADF contents among the Utah hybrids. The high digestible DM yields of hybrid X0811 emphasize the contribution of the stover fraction, in addition to the proportion of grain, to the quality of the whole-plant forage.
Keywords: Beef; Corn; Hybrid; Kansas; Utah